2013
DOI: 10.3184/175815513x13803010044073
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Characteristics of Broiler Chickens under Modified Incubation Factors

Abstract: Four groups of broiler chicken hybrid (Ross 308) eggs were incubated under different temperature and light conditions to assess the effects of both variables on musculature development. During the incubation, the first group was the control and the eggs were incubated at a temperature of 37.8 °C without light, the second group was exposed to increased temperature, while the third group was exposed to monochromatic green light. The fourth group of eggs was incubated under simultaneously changed temperature (acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Our results suggest no significant effects of genotype and muscle on the nucleo-cytoplasmic ratio where values were between 0.015 and 0.017. But Stojanović et al (2013) shows that the value of the nucleo-cytoplasmic ratio in broiler chickens Ross hybrids, at the age of 42 days was 0.15. In the same study, it was shown that age has significant influence on this parameter.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results suggest no significant effects of genotype and muscle on the nucleo-cytoplasmic ratio where values were between 0.015 and 0.017. But Stojanović et al (2013) shows that the value of the nucleo-cytoplasmic ratio in broiler chickens Ross hybrids, at the age of 42 days was 0.15. In the same study, it was shown that age has significant influence on this parameter.…”
Section: Discussionmentioning
confidence: 96%
“…These results are in accordance with authors who conclude that the autochthonous breeds have better meat quality then commercial hybrids (Pavlovski et al, 2012). In order to compare the volume density of connective tissue within the muscle of broiler (fast growing strains), Red-bro as medium growing strain and autochthonous breeds as slow-growing strains, we compared the results of our study and the results from earlier research done with broiler chickens (Stojanović et al, 2013). The results of our study showed that the volume density of connective tissue in pectoral muscle was from 16.19% at Red-bro to 26.59% at Sombor crested, while in broiler chickens the average value was 17.97 % in the pectoral muscle broiler chickens Ross 308 at 42 days (Stojanović et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Percentage measurements were performed using the M42 testing system described elsewhere [4,19,22,28], which basically consists of 21 line segments and 42 points in the testing area. For stereological analyses, the following formulas were used:…”
Section: Histological Analysismentioning
confidence: 99%